Production of Vesicular Stomatitis Virus Glycoprotein-Pseudotyped Lentiviral Vector Is Enhanced by Ezrin Silencing - Izumida, Mai; Togawa, Kei; Hayashi, Hideki; Matsuyama, Toshifumi; Kubo, Yoshinao (Frontiers in Bioengineering and Biotechnology, 2020)
Human immunodeficiency virus type 1 (HIV-1)-based viral vector is widely used as a biomaterial to transfer a gene of interest into target cells in many biological study fields including gene therapy. Vesicular stomatitis virus glycoprotein (VSV-G)-containing HIV-1 vector much more efficiently transduces various mammalian cells than other viral envelope proteins-containing vectors. Understanding the mechanism would contribute to development of a novel method of efficient HIV-1 vector production. HIV-1 vector is generally constructed by transient transfection of human 293T or African green monkey COS7 cells. It was found in this study that HIV-1 Gag protein is constitutively digested in lysosomes of African green monkey cells. Surprisingly, VSV-G elevated HIV-1 Gag protein levels, suggesting that VSV-G protects Gag protein from the lysosomal degradation. Unphosphorylated ezrin, but not phosphorylated ezrin, was detected in COS7 cells, and ezrin silencing elevated Gag protein levels in the presence of VSV-G. Expression of unphosphorylated ezrin reduced Gag protein amounts. These results indicate that unphosphorylated ezrin proteins inhibit the VSV-G-mediated stabilization of HIV-1 Gag protein. Trafficking of HIV-1 Gag-associated intracellular vesicles may be controlled by ezrin. Finally, this study found that ezrin silencing yields higher amount of VSV-G-pseudotyped HIV-1 vector.